The level of information literacy female students of The College of Computer Science and Engineering in the light of the fourth industrial revolution at The University of Jeddah - Alarjan, Rawan Abdulkreem; Al-Mohammadi, Najwa Atyan (Journal of Educational and Psychological Sciences, 2022)
This study sought to determine the level of information literacy College of Computer Science and Engineering in Jeddah University the light of The Fourth Industrial Revolution. Data were collected by adjusting a measure information literacy. The study sample, which consisted of 189 students from their various disciplines in the College of Computer Science and Engineering in Jeddah University. the researcher used the descriptive survey method, the results of the study showed that the level of the students’ acquisition of Information literacy skills was medium in general, He came in at a rate of 3.39 out of 5.00). Despite the efforts made in seeking to develop information literacy skills, especially among university students, However, the availability of information literacy among students still faces a number of challenges that prevent it from reaching the desired level; these challenges may be the lack of awareness of some students about the methods of scientific research and its importance، The lack of some students of research and investigation skills, and how to use electronic research tools, and the lack of awareness of some students in the form, place and methods of access to information, employment, and organization, and between those efforts that are made in order to achieve appropriate information literacy for students, and between the complexity and multiplicity of information literacy skills، As evidenced by the results of the current study, based on the results of the research Accordingly, the researcher made some recommendations, including enhancing the skills and awareness of information through training courses and enrichment programs, ensuring that students are informed about the Anti-Cybercrime system, examining the extent of integration in what students learn in the college, and urging students to participate in scientific forums affiliated with the University and its scientific and practical importance.